Electrospun Nanofiber/Textile Supported Composite Membranes with Improved Mechanical Performance for Biomedical Applications - Mohammed Jalalah; Adnan Ahmad; Asad Saleem; Muhammad Bilal Qadir; Zubair Khaliq; Muhammad Qamar Khan; Ahsan Nazir; M. Faisal; Mabkhoot Alsaiari; Muhammad Irfan; Saeed A. Alsareii; Farid A. Harraz (Membranes, 2022)
Textile-supported nanocomposite as a scaffold has been extensively used in the medical field, mainly to give support to weak or harmed tissues. However, there are some challenges in fabricating the nanofiber/textile composite, i.e., suitable porous structure with defined pore size, less skin contact area, biocompatibility, and availability of degradable materials. Herein, polyamide-6 (PA) nanofibers were synthesized using needleless electrospinning with the toothed wheel as a spinneret. The electrospinning process was optimized using different process and solution parameters. In the next phase, optimized PA nanofiber membranes of optimum fiber diameter with uniform distribution and thickness were used in making nanofiber membrane–textile composite. Different textile fabrics (woven, non-woven, knitted) were developed. The optimized nanofiber membranes were combined with non-woven, woven, and knitted fabrics to make fabric-supported nanocomposite. The nanofiber/fabric composites were compared with available market woven and knitted meshes for mechanical properties, morphology, structure, and chemical interaction analysis. It was found that the tear strength of the nanofiber/woven composite was three times higher than market woven mesh, and the nanofiber/knitted composite was 2.5 times higher than market knitted mesh. The developed composite structures with woven and knitted fabric exhibited improved bursting strength (613.1 and 751.1 Kpa), tensile strength (195.76 and 227.85 N), and puncture resistance (68.76 and 57.47 N), respectively, than market available meshes. All these properties showed that PA nanofibers/textile structures could be utilized as a composite with multifunctional properties.